قيم الإسلام الوسطي في كتاب اللغة العربية للمدرسة الثانوية الإسلامية - Pritasari, Shofie Asya (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
ENGLISH: Living in a social life, we need the inculcation of the values ​​of religious moderation. Because several times there are some cases that teachings of radicalism are contained in the textbook. Therefore, inculcating the values ​​of religious moderation must be applied to children in their school period as a form of anticipation from an early age. The inculcation of Islamic moderation values ​​can not only be applied in the development of attitudes in daily activities, but also can be inserted in several subject books, including Arabic language textbooks. This article aims to mention the moderate Islamic values ​​found in the 11th grade Arabic textbook of Islamic senior high school and to describe the serving form of moderate Islamic values ​​found in the 11th grade Arabic textbooks of Islamic senior high school. This research is a descriptive qualitative research. The data collection method used in this research is the documentation method on primary and secondary data sources. And the data analysis technique used is content analysis. And then the results are presented in the description serving form of moderate Islamic values ​​in the Arabic Language textbook for 11th grade of Islamic senior high school published by the Ministry of Religion and how they are served. The results of this research indicate that there are three moderate Islamic values ​​in the Arabic Language textbook for 11th grade of Islamic senior high school published by the Ministry of Religion, namely tolerance, anti-violence, and national commitment. While the serving of moderate Islamic values ​​in this book is contained in several activities such as in maharah istima', maharah qiro'ah, maharah kalam, qowaid, and also they found in several practice questions. INDONESIA: Dalam menjalani kehidupan bermasyarakat, kita membutuhkan penanaman nilai-nilai moderasi beragama. Hal ini dikarenakan beberapa kali ditemukan adanya ajaran-ajaran radikalisme yang terkandung dalam buku pelajaran. Oleh karena itu, penanaman nilai-nilai moderasi beragama juga harus diterapkan kepada anak sejak dalam masa sekolah sebagai bentuk pengantisipasian sejak dini. Penanaman nilai-nilai moderasi islam tidak hanya bisa diterapkan dalam pengembangan sikap dalam kegiatan sehari-hari, tetapi juga bisa disisipkan dalam buku-buku mata pelajaran, termasuk buku pelajaran bahasa Arab. Artikel ini bertujuan untuk mendeskripsikan nilai-nilai Islam moderat yang ada pada buku ajar bahasa Arab kelas 11 Madrasah Aliyah dan mendeskripsikan bentuk penyajian nilai-nilai Islam moderat yang ada pada buku ajar bahasa Arab kelas 11 Madrasah Aliyah. Penelitian ini merupakan penelitian kualitatif deskriptif. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode dokumentasi pada sumber data primer dan sumber data sekunder. Dan teknik analisis data yang digunakan adalah analisis isi. Kemudian hasilnya disajikan dalam bentuk deskripsi mengenai nilai-nilai Islam moderat yang ada di dalam Buku Ajar Bahasa Arab Kelas 11 Madrasah Aliyah terbitan Kementerian Agama dan bagaimana bentuk penyajiannya. Hasil dari penelitian ini menunjukkan bahwa terdapat tiga nilai Islam moderat dalam Buku Ajar Bahasa Arab Kelas 11 Madrasah Aliyah terbitan Kementerian Agama, yaitu toleransi, anti kekerasan, dan komitmen kebangsaan. Sedangkan penyajian nilai-nilai Islam moderat dalam buku ini terdapat dalam kegiatan maharah istima’, maharah qiro’ah, maharah kalam, qowaid, dan terdapat dalam soal-soal latihan juga.